Big Picture Strategy - Dapena-Barón, Marta (Wiley, 2021)
Develop winning brand strategies by focusing your team on the key strategic choices that drive organizational growth and learning. This book presents a system of six practical choices that articulate exactly how to launch and grow brands. Big Picture Strategy shows readers how limiting and focusing the strategic options available to company stakeholders can unlock previously inaccessible levels of productivity and growth. Strategist, consultant, and author Marta Dapena Barón describes the six key decisions facing organizations and teams today and how to develop a winning strategy by approaching these decisions systematically. The book includes discussions of: The critical choices that leaders must make to define a marketing strategy and to align their teams to be able to execute on it The four strategies companies use to launch and grow brands successfully How to use strategy-integrated metrics to promote continuous learning in organizations How to increase communications efficiency in commercial organizations through the use of a common vocabulary to frame customer-based issues Unlike many of its competitors, Big Picture Strategy does not pretend that your organization has unlimited resources or capacity to pursue every area of possible strategic advantage. Instead, the author lays out a systematic and integrated choice-based framework that will drive growth in your organization for years to come.